Hair Graying Regulators Beyond Hair Follicle - Chen, Jing; Zheng, Yixin; Hu, Chen; Jin, Xuexiao; Chen, Xiaoping; Xiao, Ying; Wang, Chaochen (Frontiers in Physiology, 2022)
Hair graying is an interesting physiological alteration associated with aging and certain diseases. The occurrence is due to depigmentation of the hair caused by depletion and dysfunction of melanocyte stem cells (MeSCs). However, what causes the depletion and dysfunction of MeSCs remains unclear. MeSCs reside in the hair follicle bulge which provides the appropriate niche for the homeostasis of various stem cells within hair follicle including MeSCs. In addition to local signaling from the cells composed of hair follicle, emerging evidences have shown that nerves, adipocytes and immune cells outside of hair follicle per se also play important roles in the regulation of MeSCs. Here, we review the recent studies on different cells in the MeSCs microenvironment beyond the hair follicle per se, discuss their function in regulating hair graying and potentially novel treatments of hair graying.